2016
DOI: 10.1095/biolreprod.116.143461
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stro1+/CD44+ stem cells in myometrial physiology and uterine remodeling during pregnancy†

Abstract: Regulation of myometrial functions during pregnancy has been considered the result of the integration of endocrine and mechanical signals. Nevertheless, uterine regeneration is poorly understood, and the cellular source within the gravid uterus is largely unexplored.In this study, we isolated and quantified the myometrial stem cells (MSC) population from pregnant female Eker rat uteri, by using Stro1/CD44 surface markers. We demonstrated that prior parity significantly increased the percentage of Stro1+/CD44+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…To confirm the presence of CSCs, western blot analysis was used to identify the mesenchymal and cSc markers STro-1, cd44 and STaT3 (36,37). The results indicate the presence of these markers with comparable band densities and almost identical average ods between the three markers of interest (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…To confirm the presence of CSCs, western blot analysis was used to identify the mesenchymal and cSc markers STro-1, cd44 and STaT3 (36,37). The results indicate the presence of these markers with comparable band densities and almost identical average ods between the three markers of interest (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…During pregnancy, the human uterus undergoes a 500- to 1000-fold increase in volume and a 24-fold increase in weight, which demonstrates the remarkable capacity of the myometrium to regenerate and remodel itself [ 3 ]. Although the regulation of myometrial functions during pregnancy and labor is mainly the result of the integration of endocrine and mechanical signals, it is reasonable to assume that the impressive myometrium regenerative ability must be tightly connected to a resident somatic stem cell population [ 3 , 18 ]. There is increasing evidence that adult stem cells not only reside in highly regenerative tissue like bone marrow [ 25 , 26 ], intestine, and epidermis [ 27 , 28 ] but are also found in most tissue where they function to maintain hemostasis by replacing cells lost by apoptosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myometrial smooth muscle cells have receptors for progesterone and estrogen, and they could play an important role in upregulating the proliferation of Oct-4/CD44/Nanog myometrial stem cells in murine myometrium, especially during pregnancy, via paracrine pathway [ 18 ]. Here, we demonstrated that both ER and PR are indeed abundantly expressed in the murine myometrium at ages 1, 3, and 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations